Educandy Learning Media in Indonesian Language Syllable Learning Media to Improves Reading and Writing Literacy - Tarisna, Kadek Sri; I Nyoman Laba Jayanta; Putu Rahayu Ujianti (Universitas Pendidikan Ganesha, 2025)
Students have very low literacy skills. This is because the supporting media is still conventional in syllable learning activities. Based on this, this study aims to develop educated learning media to improve the literacy of reading and writing of grade I elementary school students. This type of research is research and development or Research and Development using the ADDIE model. The subjects of the study were three experts consisting of 2 material experts, 2 media experts, and 2 practitioners. The subjects of the product trial included individual trials of 3 students and small group trials of 6 students. The subjects of the product trial included individual trials of 3 students and small group trials of 6 students. The data collection method used the observation method and questionnaire. The data collection instrument used a rating scale. The data analysis techniques were quantitative descriptive data analysis, quantitative descriptive analysis, and inferential statistics. The study's results were the assessment of learning material experts, namely 91%, who had very good qualifications. The evaluation of learning media experts was 96% in very good qualifications. The results of the practicality test from the teacher obtained a percentage of 93.2%. The results of individual trials were 94%, and the results of small group trials were 95% with very good qualifications. The t-test results showed a significant difference in student learning outcomes before and after participating in learning using educational learning media. Thus, the use of educational media is effective in improving students' reading and writing literacy.